A wide-angle broadband electromagnetic absorbing metastructure using 3D printing technology. (October 2021) - Duan, Yubing; Liang, Qingxuan; Yang, Zhen; Li, Zhaohui; Yin, Haoyu; Cao, Yi; Li, Dichen
Graphical abstract: Highlights: A complex gradient composite metastructure was fabricated by 3D printing technology. This metastructure has the broadband and strong microwave absorption. Maintaining broadband absorption under wide-angle for different polarization. Low loss materials addition could satisfy the high-performance microwave absorption. Abstract: Gradient composite metastructures have been demonstrated in effectively improving the microwave absorbing performance. However, the preparation of the complex structures still remains challenging. Herein, a complex gradient composite microwave absorbing metastructure is designed and fabricated by the low cost, high-efficiency fused deposition modeling of 3D printing technologies. The metastructure is composed of flaky carbonyl iron particles and Polyether-ether-ketone composite which demands only 50% loss material mass addition. Structural parameters are investigated and optimized for absorbing bandwidth and reflectivity intensity. Simulations and experiments demonstrate that the designed complex gradient metastructure with the thickness of 10 mm can achieve the −10 dB absorbing bandwidth in the frequency range from 5.1 to 40 GHz, and the absorbing bandwidth corresponding to −15 dB in 7.7–14.7 GHz and 22.6–36.3 GHz. Meanwhile, this metastructure also can maintain the broadband and strong microwave absorption with incident angle from 0° to 55° for transverse electric polarization and 0° to 70° for transverse magnetic polarization. Moreover, the proposed metastructure is also demonstrated with good compression strength which shows preferable mechanical stability. This work provides a simple and promising route of broadband and wide-angle microwave strong absorption for practical application.